Programa educativo de sociograma literario en el mejoramiento de la comprensión de textos escritos en inglés en estudiantes de primer grado de secundaria en la Institución Educativa Pública Maynas de Iquitos 2023 - Merma Tenazoa, Rafael Oscar (2025)
The educational program associated with the application of literary sociograms aimed at evaluating its effect on the comprehension of written texts in English among the population (N=258) related to the students of the Maynas educational institution, located in Iquitos in the year 2023. This research included 32 students from section A, who formed the control group, and 32 students from section B, who constituted the experimental group, making a total sample of 64 students. The study is evaluative in nature and follows a field design; it is univariable, cross sectional, and quasi-experimental, supported by the application of pre- and post tests. The results of both groups showed a significant increase in the average score of the experimental group, with 12.917 > 9.514 on a vigesimal scale of 0 20. Consequently, it is concluded that there was a significant improvement in the variable referred to as text comprehension, with a p-value of 0.000, which is lower than α=0.05.